The genome sequence of the Red Chestnut moth, Cerastis rubricosa (Schiffermüller, 1775) - Boyes, D; Holland, PWH (F1000Research, 2024)
We present a genome assembly from an individual male Cerastis rubricosa (the Red Chestnut moth; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 678.7 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.39 kilobases in length. Gene annotation of this assembly on Ensembl identified 18,784 protein coding genes.